PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ICT DI KELAS IV SDN 34 SEBERANG PALINGGAM KOTA PADANG - Mita Vidi Yanti; Ade Irma Suryani (Jurnal Riset Pendidikan Dasar Dan Karakter, 2021)
This research is motivated by the importance of developing learning media used by teachers in the learning process. The main objective of this research is to produce an ICT-based learning media product in the form of Macromedia Flash 8 which refers to the 2013 Curriculum and to describe the quality of ICT-based learning media products referring to the 2013 SD Curriculum. This type of research is development research. The development procedure used in this study consists of 4 steps, namely: 1) Define, 2) Design, 3) Development, 4) Dissemination (Dissemination). The instrument used in this study was the learning media validation instrument sheet. The validation instrument was used to determine the validity of the designed Macromedia Flash 8 media. Validation is carried out by design experts and material experts. The results showed that ICT-based learning media in Integrated Thematic learning in grade IV SD is very valid when used in learning. This is evidenced by (1) the results of expert validation "Y" in ICT-based learning media are included in the criteria of "very valid" with a score of 95.83%. (2) the results of expert validation "FOF" ICT-based learning media are included in the "very valid" criteria with a score of 95.83%. (3) the results of expert validation "A" ICT-based learning media are included in the criteria "very valid" with a score of 93,75%. Thus, the developed ICT-based learning media is very valid if used as a medium in the learning process.